2017
DOI: 10.1002/jsfa.8543
|View full text |Cite
|
Sign up to set email alerts
|

In vitro renin–angiotensin system inhibition and in vivo antihypertensive activity of peptide fractions from lima bean (Phaseolus lunatus L.)

Abstract: Peptide fractions from lima bean Phaseolus lunatus protein hydrolysates exhibit both in vitro and in vivo antihypertensive activity. Bioactive peptides from lima bean have potential applications as ingredients in functional foods. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 24 publications
1
33
1
2
Order By: Relevance
“…The results generally suggest that pigeon pea hydrolysates may have potential as antihypertensive agents. The results for PPHPp were higher than 10.53% reported for pepsin‐pancreatin lima bean hydrolysate (Ciau‐Solís, Acevedo‐Fernández, & Betancur‐Ancona, ). The observed differences in the ACE‐inhibitory activity have been attributed to differences in legume type, peptide mixture composition, changes in the parameters of the digestion process (enzyme, pH, time, temperature, substrate/enzyme ratio, etc.)…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The results generally suggest that pigeon pea hydrolysates may have potential as antihypertensive agents. The results for PPHPp were higher than 10.53% reported for pepsin‐pancreatin lima bean hydrolysate (Ciau‐Solís, Acevedo‐Fernández, & Betancur‐Ancona, ). The observed differences in the ACE‐inhibitory activity have been attributed to differences in legume type, peptide mixture composition, changes in the parameters of the digestion process (enzyme, pH, time, temperature, substrate/enzyme ratio, etc.)…”
Section: Resultscontrasting
confidence: 62%
“…Ciau‐Solís et al. () reported a renin inhibitory activity of 5.5% for lima bean hydrolysate obtained using pepsin‐pancreatin sequential hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, Ciau‐Solís et al . () reported that peptide fractions from P. lunatus hydrolysate with molecular weight >1000 Da had higher ACE‐I inhibitory activity than those with < 1000 Da. However, further purification and physicochemical characterisation studies of ACE‐I inhibitory peptides from PG‐C dialysate must be done to confirm these results.…”
Section: Resultsmentioning
confidence: 99%
“…P. lunatus hydrolysate was obtained sequentially by Alcalase ® and Flavourzyme ® hydrolysis according to Ciau‐Solís et al . (). Degree of hydrolysis (DH) was calculated according to Nielsen et al .…”
Section: Methodsmentioning
confidence: 97%
“…A protein concentrate was made according to Betancur-Ancona et al (2004). P. lunatus hydrolysate was obtained sequentially by Alcalase Ò and Flavourzyme Ò hydrolysis according to Ciau-Sol ıs et al (2018). Degree of hydrolysis (DH) was calculated according to Nielsen et al (2001).…”
Section: Protein Hydrolysatementioning
confidence: 99%